In order to integrate

$$\int \sqrt{\frac{x}{x+1}}dx$$

I did:

$$x = \tan^2\theta $$

$$\int \sqrt{\frac{x}{x+1}}dx = \int\sqrt{\frac{\tan^2(\theta)}{\tan^2(\theta)+1}} \ 2\tan(\theta)\sec^2(\theta)d\theta = \int \frac{|\tan(\theta)|}{|\sec^2(\theta)|}2\tan(\theta)\sec^2(\theta)d\theta = \int \tan^3\theta d\theta = \int\frac{\sin^3 \theta}{\cos^3 \theta}d\theta$$

$$p = \cos\theta \implies dp = -\sin\theta d\theta$$

$$\int\frac{\sin^3 \theta}{\cos^3 \theta}d\theta = -\int\frac{(1-p^2)(-\sin\theta)}{p^3 }d\theta = -\int \frac{1-p^2}{p^3}dp = -\int \frac{1}{p^3}dp +\int \frac{1}{p}dp = -\frac{p^{-2}}{-2}+\ln|p| = -\frac{(\cos\theta)^{-2}}{-2}+\ln|\cos\theta|$$

$$x = \tan^2\theta \implies \tan\theta= \sqrt{x}\implies \theta = \arctan\sqrt{x}$$

$$= -\frac{(\cos\arctan\sqrt{x})^{-2}}{-2}+\ln|\cos\arctan\sqrt{x}|$$

But the result seems a little bit different than wolfram alpha. I Know there may be easier ways to solve this integral but my question is about this method I choose, specifically.

Is the answer correct? Also, if it is, is there a way to reduce $\cos\arctan$ to something simpler?

  • $\begingroup$ It looks like things started falling apart with the square root. You never took the square root of the denominator. And the next step doesn't appear to follow. $\endgroup$ – Mike Feb 10 '15 at 21:55
  • $\begingroup$ $\sqrt{\tan^2(\theta)+1}=\sqrt{\sec^2(\theta)}=|\sec^2(\theta)|$ Also $\endgroup$ – kingW3 Feb 10 '15 at 21:57
  • $\begingroup$ @Mike :'( $\frac{}{}$ $\endgroup$ – Guerlando OCs Feb 10 '15 at 22:03
  • $\begingroup$ @kingW3 $\sqrt{\tan^2\theta+1}=\sqrt{\sec^2\theta}=|\sec\theta|$ $\endgroup$ – Mike Feb 10 '15 at 22:10
  • $\begingroup$ @Mike That was supposed to be the point of my comment about the mistake,I guess I was too hasty $\endgroup$ – kingW3 Feb 10 '15 at 22:18

For the last question, you have a triangle with side lengths $1,x,\sqrt{x^2+1}$ to have tangent $x$. That triangle has cosine $\frac{1}{x^2+1}$. Hence $$\cos \arctan x=\frac{1}{\sqrt{x^2+1}}$$


Let $u=\sqrt{\frac{x}{x+1}}$. Then $$ \begin{align} \int\sqrt{\frac{x}{x+1}}\,\mathrm{d}x &=\int u\,\mathrm{d}\frac{u^2}{1-u^2}\\ &=\frac12\int u\,\mathrm{d}\left(\frac1{1-u}+\frac1{1+u}\right)\\ &=\frac12\int u\left(\frac1{(1-u)^2}-\frac1{(1+u)^2}\right)\,\mathrm{d}u\\ &=\frac12\int\left(\frac1{(1-u)^2}-\frac1{1-u}+\frac1{(1+u)^2}-\frac1{1+u}\right)\,\mathrm{d}u\\ &=\frac12\left(\frac1{1-u}+\log(1-u)-\frac1{1+u}-\log(1+u)\right)+C\\ &=\frac{u}{1-u^2}+\frac12\log\left(\frac{1-u}{1+u}\right)+C\\[6pt] &=\sqrt{x(x+1)}+\log\left(\sqrt{x+1}-\sqrt{x}\right)+C \end{align} $$


Consider $$I=\int\sqrt{\frac{x}{1+x}}dx.$$ We proced by the change of variable $u=\sqrt{1+x}$, $du=\frac{1}{2\sqrt{1+x}}$dx and $x=u^2-1,$ which gives $$I=2\int \sqrt{u^2-1}\ du=u\sqrt{u^2-1}-\log\left(u+\sqrt{u^2-1}\right)+C,$$ see https://owlcation.com/stem/How-to-Integrate-Sqrtx2-1-and-Sqrt1-x2 for more informations. The calculations ends by replacing value of u by $\sqrt{x^2-1}$.


Another aproach to the integral : substitution $x=t^2$

$$\int\sqrt{\frac{x}{x+1}} \;\mathrm{d}x = \int\frac{2t^2 \mathrm{d}t}{\sqrt{t^2+1}} $$

By per partes :

$$I = \int\frac{t^2 \mathrm{d}t}{\sqrt{t^2+1}} = t\sqrt{t^2+1}-\int\sqrt{t^2+1}\;\mathrm{d}t = t\sqrt{t^2+1}-\int\frac{t^2+1}{\sqrt{t^2+1}}\;\mathrm{d}t $$

Ergo $$I = t\sqrt{t^2+1}-I-\operatorname{arcsinh}{t}$$ So, because original integral was $2I$, solution is therefore :

$$\int\sqrt{\frac{x}{x+1}} \;\mathrm{d}x = \sqrt{x}\sqrt{x+1}-\operatorname{arcsinh}{\sqrt{x}} +C $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.